Trajectories of sickness absence after road traffic injury: a Swedish register-based cohort study - Marie Hasselberg; Hans-Yngve Berg; Ritva Rissanen; Yajun Liang; Jette Moeller; Alicia Nevriana (BMJ Open)
Objectives Despite much focus on the health impact of road traffic injury (RTI) on life, there is a lack of knowledge of the dynamic process of return to work following RTI and its related factors. The aim of this study was to identify longitudinal patterns of sickness absence (SA) following RTI, to examine the patterns’ interplay with health-related quality of life (HRQoL) and to determine if there are differences, regarding the patterns and interplay, according to injury severity.Design A register-based prospective cohort study.Setting Administrative data on RTI in Sweden from the Swedish Traffic Accident Data Acquisition System (STRADA) and Swedish Social Insurance data.Participants Individuals suffering an RTI (total n=4761) were identified in STRADA between 1 January 2007 and 31 December 2009. A total of 903 of these met the inclusion criteria for the current study and were included.Primary and secondary outcome measures The primary outcome measure was SA following RTI. The secondary outcome measure was HRQoL.Results Three distinct patterns of SA were identified; ‘Stable’, ‘Quick decrease’ and ‘Gradual decrease’. The patterns differed in the number of initial SA days and the rate of reduction of SA days. After 3 years, all three patterns had almost the same level of SA. Higher injury severity and a higher number of SA days had a negative interplay with HRQoL. Participants who initially had a higher number of SA days were more likely to report a low HRQoL, indicating that people with a slower return to work are more vulnerable.Conclusion The study highlights the heterogeneity of return to work after an RTI. People with a more severe injury and slower pace of return to work seem to be more vulnerable with regards to HRQoL loss following RTI.